Three new species of the genus Araeopteron Hampson, 1893 (Lepidoptera, Erebidae, Boletobiinae) from the Xizang Autonomous Region, China with an updated list of the world species - Hui Lin Han; Vladimir S. Kononenko (ZooKeys, 2021)
Three new species of the genus Araeopteron Hampson, 1893: A. dawai sp. nov., A. medogensis sp. nov. and A. tibeta sp. nov. are described from Motuo (= Medog) County of the Xizang Autonomous Region (= Tibet), China. The imagines as well as the male genitalia are illustrated. A checklist of the 45 species of the genus Araeopteron in the world fauna is presented, including recently and presently described species.